L’initiative de Gorbatchev à Mourmansk et les mesures de restauration de la confiance dans l’Arctique - Issaraelian, Evgenia (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
In his speech at Murmansk on October 1, 1987, General Secretary Gorbachev presented a programme to radically lower the level of military confrontation in the Arctic and proposed a number of confidence-building measures. The Murmansk initiative followed numerous previous proposals along the same line, going back to the nineteen fifties. The political and military aspects of the initiative are linked to the Soviet concept of international security. There are three main elements to this concept: first, the impossibility, to-day, of insuring a country's security by military means alone; second, security must be mutual between the Soviet Union and the United States and it must be universal in the rest of the world; third, security must be comprehensive and must include the military, political, economic and humanitarian dimensions. Specifically on northern security, it must be noted that the Soviet Union is quite vulnerable in the Arctic, with about half of its total land mass north of the 60th parallel. Also, the Arctic offers the shortest route for ICBMS, SLBMs and strategic bombers. Consequently, international security in the Arctic dictates confidence-building measures. The Murmansk initiative represents a significant contribution to the whole process of confidence-building by proposing, in particular: to limit the number of large exercises by naval and air forces in the Northern seas; to invite observers to such exercises; to include Barents Sea, along with other Northern seas, in a zone of peace; to ban anti-submarine activities in agreed areas of the Northern and Western Atlantic; to include the reduction of military activities in the Arctic on the agenda of the second stage of the Conference on CBM and Disarmement in Europe; to reduce naval activities in international straits; and to pursue the establishment of a Nordic nuclear weapon-free zone for which the Soviet Union would act as guarantor.